PIJAT BAYI DAN PENURUNAN KADAR BILIRUBIN BAYI IKTERIK: A SCOPING REVIEW - Larasati, Disa; Putri, Noviyati Rahardjo (Journal of Midwifery Science: Basic and Applied Research, 2023)
Jaundice is a disorder manifested by yellow discoloration of the skin, sclera and mucous membranes due to an increase in total serum bilirubin (TSB) in the circulation which is usually called hyperbilirubinemia. The aim of this study was to determine the effectiveness of massage to reduce bilirubin levels in icteric babies undergoing phototherapy. The type of research was a systematic review with PRISMA method. Data was accessed from; Google Scholar, PubMed, Research gate, One search, Garuda in the period 2013 to 2023. The article is original research, written in English or Indonesian and the research design is in the form of experimental research with designs: quasi experiments and randomized controlled trials. The number of articles that correspond is 7 articles. The research subjects were healthy babies and babies with jaundice. The results of the systematic review are that regular massage therapy in infants with jaundice undergoing phototherapy has an effective effect in reducing total serum bilirubin (TSB), increasing bilirubin excretion with defecation, reducing the duration of hospitalization. This complementary therapy is an effort to increase the effectiveness and efficiency of treating icteric babies during the hospitalization period.